Tempo de equilíbrio na criopreservação do sêmen: efeitos sobre características de motilidade e de integridade das membranas espermáticas de touros Gir leiteiro - Ticiano Guimaraes Leite (2008)
Effects on semen cryopreservation of two extenders (TRIS and Bioxcell) and three equilibration times (T0, T2 and T4 hours) on sperm movement, integrity of plasma and acrosomal membranes, mitocondrial function was evaluated. Interactions between extenders and equilibration times for Total Motility (MOT, %), Progressive Motility (PROG, %), and percentage of spermatozoa with intact plasma and acrosomal membranes (IPIA, %) and damaged acrosomal membrane (DA, %) was registered. No differences (P >0.05) between T2 and T4 for MOT and PROG, within each extender were observed. T0 showed the lowest values (P<0.05), differing from T2 and T4, for MOT, PROG, integrity of plasma and acrossomal membranes, for both extenders. No differences for T0 were observed between extenders (P >0.05) for MOT, PROG, IPIA and DA. TRIS showed the highest results for MOT, PROG, IPIA and the lowest results for DA in T2 and T4, as well as the lowest proportion of damaged plasma membrane (DPM,%). T4 showed the highest results (P<0.05) for the main parameters studied (MOT, PROG, IPIA). No effect of extender or equilibration time was registered for mitochondrial function (P>0.05). Treatment using TRIS and T4 showed the biggest results (P< 0.05) in relation to MOT, PROG, IPIA and the lowest results (P< 0.05) for DPM and DA. The combination of TRIS and T4 was the best method of bovine semen cryopreservation. It was concluded that equilibration time is needed for preservation of MOT, PROG and integrity of sperm membranes. At least 4h of equilibration time is needed for high sperm survival rates